2003
DOI: 10.1016/s0960-9822(03)00135-0
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Cortical Computation

Abstract: Electrophysiological recordings show that individual neurons in cortex are strongly activated when engaged in appropriate tasks, but they tell us little about how many neurons might be engaged by a task, which is important to know if we are to understand how cortex encodes information. For human cortex, I estimate the cost of individual spikes, then, from the known energy consumption of cortex, I establish how many neurons can be active concurrently. The cost of a single spike is high, and this severely limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
746
6
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 930 publications
(779 citation statements)
references
References 22 publications
26
746
6
1
Order By: Relevance
“…Experimental studies comparing electrophysiological measurements with BOLD and CBF changes have found that the hemodynamic responses correlate better with local mean field potential, rather then local spiking rates, suggesting that the hemodynamic response is dominantly driven by input synaptic activity rather than output spiking activity (Lauritzen, 2001;Lauritzen and Gold, 2003;Logothetis, 2002;Logothetis et al, 2001). Theoretical analyses of the energy budget for neuronal signaling provide some support for this picture as well (Attwell and Laughlin, 2001;Lennie, 2003). The primary expenditure of energy is required to restore the ion gradients degraded during neural activation.…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…Experimental studies comparing electrophysiological measurements with BOLD and CBF changes have found that the hemodynamic responses correlate better with local mean field potential, rather then local spiking rates, suggesting that the hemodynamic response is dominantly driven by input synaptic activity rather than output spiking activity (Lauritzen, 2001;Lauritzen and Gold, 2003;Logothetis, 2002;Logothetis et al, 2001). Theoretical analyses of the energy budget for neuronal signaling provide some support for this picture as well (Attwell and Laughlin, 2001;Lennie, 2003). The primary expenditure of energy is required to restore the ion gradients degraded during neural activation.…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…At the systems level, this paradigm shift was prompted by two major findings. First, although the human brain represents only 2% of total body mass, its intrinsic activity consumes 20% of the body's energy, most of which is used to support ongoing neuronal signalling ( [5][6][7][8][9], but see also [10]). Task-related increases in neuronal metabolism are generally small (less than 5%) when compared with this large intrinsic energy consumption (for a recent review, see [9]).…”
Section: Importance Of Intrinsic Activitymentioning
confidence: 99%
“…13 C MRS findings in the human cortex have been generally consistent with the rat results (6). However, there remain questions as to how well the energy costs of specific subcellular processes needed to support synaptic transmission and conduction are conserved over different activity levels and/or across species.Recent bottom-up energy budgets for gray matter in the mammalian brain have attempted to understand the energetic costs of neuronal and glial electrical and neurotransmission events occurring in the neuropil (7,8) by calculating the ATP used per neuron for signaling (P s ) and nonsignaling (P ns ) events. In the awake cortex, the total ATP used per unit cortical volume per unit time (E tot ; in units of ATP/s per centimeter 3 ) was determined by multiplying the P s (in units of ATP/neuron per spike) and P ns (in units of ATP/neuron per second) parameters with cellular densities (η) and average cortical firing rates (<f>) to give signaling (Es) and nonsignaling (Ens) components,…”
mentioning
confidence: 99%